Organizational Work System as the Predictor of Creative Performance: A New Approach to the Learning Method System of Comprehensive Systems and Expansion of Research Field - Zhiliang Lyu; Chengao Zhang; Xiu Jin (Systems)
Previous researchers have questioned and attempted to verify whether the association between organizational work system and individual and organizational performance indicates causality. A work system is a comprehensive concept; it may be of various types, and gaps exist between the type of organizational work system and performance. To fill these gaps, we investigated the causal relationship between how a high-performance work system improves creative performance via work involvement through social exchange theory, expectancy theory, and the ability–motivation and opportunity framework. Therefore, we established an amalgamated research framework that uses the moderated mediation model of learning method system of comprehensive systems to facilitate creative performance. To verify the above, this study conducted an empirical study targeting 315 organizational members working in Chinese small and medium-sized enterprises (SMEs). For empirical analysis, we utilized SPSS Macro Process, AMOS, and SmartPLS 4 Program. We found that high-performance work systems significantly improve work involvement and creative performance. Additionally, work involvement acts as a mediator between high-performance work systems and creative performance. However, the moderating effect of the learning method system of comprehensive systems was not significant. Overall, this research was conducted in consideration of the fact that there is a considerable lack of empirical research verifying the relationship between high-performance work systems and creative performance that promotes survival and competitiveness for SMEs. In addition, the learning method system of comprehensive system has not been studied actively and it was utilized with the expectation that it would be a variable that would receive new attention through this study. Finally, this research is expected to contribute to the research fields of SMEs and organizational work systems.